PEMERINTAHAN DEMOKRASI PERSFEKTIF MASYARAKAT TOMANURUNG KEDATUAN LUWU - Syukur, Syamzan (RIHLAH, 2014)
This paper reveals that the public administration of Tomanurung at Kedatuan Luwu that appeared in the XI-XV century has been implementing democracy model of government. Despite the model of that democratic government was not exactly same with democracy right now, but its interesting that people in the government as supporting traditional communities have been able to devise a system of government where the people have a hand in determining the model or system of government. Supporting community has reached the stage of thinking that people have the right communities in making decisions that can change their lives through the representation of all groups. Community of Tomanurung at Kedatuan Luwu without the outside influences hase dispensing system of democratic governance. Democracy interpreted to allow citizens to participate, either directly or through representatives in formulating and developing the system of government. So, democracy of kedatuan Luwu take the last model of democracy that democracy is understood to allow citizens to participate through representatives.